Redefines Vitality In Primary Schools Based On The Evaluation And Analysis Of The Needs Of Children - Alizade, Meisam Sabz; Eyni, Mahmood; Asadi, Mona; Arshagi, Mohammad (The Turkish Online Journal of Design Art and Communication, 2016)
Importance of educational facilities, especially schools and their impact on children, has caused particular attention to this issue is. As far as a variety of sources in different countries in this regard is provided. Since the main users of these spaces children (children at the age of 7-12 years), they vary according to the specific needs and characteristics of specific areas is essential in planning and design. The happiness is one of the important factors in child protection matters and mental health, mental and physical he provides. In this article we examined the children's educational space.This is what needs to be addressed and that children in this environment ,and is it possible to provide specific spatial pattern, to create a favorable environment for teaching children? To achieve these objectives, using a hybrid approach, drawing 50 children with observations analyzed and evaluated. The results indicate that with regard to these requirements and integrate them with solutions derived from previous research, Can be a certain way, to strengthen the vitality of educational facilities children. Some of these solutions are use the new furniture, the use of bright colors in Building facades.
Keywords: Children; Teaching Space; Vitality; Primary Schools